Students’ Elementary Literacy Skill And Critical Thinking Skill Supported By School Literacy Program (SLP) - Nirmala, Sri Dewi; Rahman, R.; Musthafa, B (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
The literacy skills of elementary school students in Indonesia, according to international instructional survey data such as PISA and PIRLS are generally at low ability level. Starting from this condition, the government then launched the School Literacy Program (SLP) which is in sync with the implementation of Curriculum 2013. This study aims to analyze and calculate the difference of literacy ability and students’ fourth graders critical thinking in schools that organize SLP in three areas of the village, transitions, and cities located in Sukabumi Indonesia. The results showed that the students' fourth-grade literacy ability at the SLP organizing school was at a low level of 66.89, the middle level 55, the high level 54.67, and the advanced level of 55.89. The students' critical thinking ability is at a low level of 82.94, 55.33 and 55.67. Based on the results of this study, it can be concluded that fourth graders students’ literacy ability at school organizer SLP in Sukabumi is at low level / factual literal. While fourth graders students’ critical thinking was able to reach low levels.